Early steps in the production of sensory neurons by the neurogenic placodes. - Begbie, J; Ballivet, M; Graham, A (2002)
Neurogenic placodes are specialized regions of the embryonic ectoderm that generate the majority of the neurons of the cranial sensory ganglia. Here we have accurately determined the onset of neurogenesis in each of the placodes in the chick, and we have also analyzed the expression profiles of genes that are believed to be involved in determining the types of sensory neurons produced by each placode. Interestingly, we find that there is a major difference in the expression domains of neurogenin-1 and neurogenin-2 in the chick, when compared with those reported for the mouse. We do find, however, that Brn-3a and Phox-2a and Phox-2b which are also associated with the specification of neuronal type are expressed in the same domains in the chick as they are in the mouse. These results suggest that neurogenin-1 and neurogenin-2 are functionally interchangeable in neurogenic placodes. We have also found major differences between the ophthalmic and maxillomandibular trigeminal placodes, and while all of the other placodes generate mitotically active cells the ophthalmic trigeminal placode seems to throw off postmitotic neuronal cells.